The influence of health sciences librarianship courses on the career of the BLIS alumni of UP SLIS - Dela Peña, Ma. Charina M.; Santos, Mark Anthony A. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
The field of librarianship found one of its forte in the health sciences. Health sciences librarians have a special knowledge in quality health information sources and have a direct influence on the quality of patient care. As information professionals, we need to keep up with the changing and current demands of our clientele. This study focused on the influence of health sciences librarianship subjects offered by UP SLIS in the work of its graduates of the Bachelor of Library and Information Science program. Using an online survey questionnaire, respondents assessed which LIS 140 series subjects are most often applied in actual work.

The top health sciences librarianship topic for each course that has application in the work of the respondents are Resources in Basic, Clinical and Allied Health Sciences of LIS 140 and expert Searching / Mediated Literature Searching of LIS 141, LIS 140 was determined by the respondents as the most useful subject among the LIS 140 series.

Graduates who have focused on health science types of work have job titles that include science research specialist, medical student, and general physician.
Thesis
Keywords: University of the Philippines -- School of Library and Information Studies -- Alumni and alumnae; Health sciences librarianship -- Study and teaching -- Philippines; Library schools -- Curricula -- Philippines; Library and information science graduates -- Employment -- Philippines